Strategic Management of Tourism at Gangga Buyan Pancasari Tourism Park - Made Sera Septiani; Ni Wayan Gita Sadhana Savitri (Pubfine Media Group, 2025)
Introduction: In the era of modern tourism, proper management is key to maintaining a balance between economic growth, environmental preservation, and the well-being of local communities. Gangga Buyan Pancasari Tourism Park possesses natural potential as an ecotourism-based attraction, yet it faces various challenges in terms of management and environmental sustainability. Methods: This study aims to identify the current tourism management practices and analyze sustainable and effective tourism management strategies based on management capacity. Data were collected through observation, in-depth interviews, and documentation, including recordings and notes. Qualitative data were analyzed using NVivo software, and the management strategies were formulated through a SWOT analysis. Results: The management of Gangga Buyan Pancasari Tourism Park is currently handled by BUMDes Panca Giri Kencana; however, internal conflicts among stakeholders still exist. The tourism management strategy focuses on sustainability, active community participation, and environmental protection. The strategies include: (1) S-O: development of online media, collaboration between village and regional governments; (2) S-T: promotion of tourist environmental awareness programs, development of nature, cultural, and spiritual events; (3) W-O: transparency in retribution use, utilization of temple land (pelaba pura) for tourism activities; and (4) W-T: disaster mitigation planning and pentahelix synergy in management. Conclusion: Sustainable tourism management in Gangga Buyan Pancasari requires collaborative governance, community engagement, environmental protection, and strategic planning to address existing internal challenges and maximize ecotourism potential.